Use of Project ECHO to promote evidence based care for justice involved adults with opioid use disorder. Issue 1 (1st December 2022) - Adams, Zachary W.; Agley, Jon; Pederson, Casey A.; Bell, Lauren A.; Aalsma, Matthew C.; Jackson, TiAura; Grant, Miyah T.; Ott, Carol A.; Hulvershorn, Leslie A.
Abstract: Background: People with opioid use disorders (OUDs) are at heightened risk for involvement with the criminal justice system. Growing evidence supports the safety and effectiveness of providing empirically supported treatments for OUD, such as medications for OUD (M-OUD), to people with criminal justice involvement including during incarceration or upon reentry into the community. However, several barriers limit availability and accessibility of these treatment options for people with OUDs, including a shortage of healthcare and justice professionals trained in how to implement them. This study evaluated a novel education program, the Indiana Jail OUD Treatment ECHO, designed to disseminate specialty knowledge and improve attitudes about providing M-OUD in justice settings. Methods: Through didactic presentations and case-based learning (10 bimonthly, 90-min sessions), a multidisciplinary panel of specialists interacted with a diverse group of community-based participants from healthcare, criminal justice, law enforcement, and related fields. Participants completed standardized surveys about OUD knowledge and attitudes about delivering M-OUD in correctional settings. Thematic analysis of case presentations was conducted. Results: Among 43 participants with pre- and post-series evaluation data, knowledge about OUD increased and treatment was viewed as more practical after the ECHO series compared to before. Cases presented during the program typically involved complicated medical and psychiatric comorbidities, and recommendations addressed several themes including harm reduction, post-release supports, and integration of M-OUD and non-pharmacological interventions. Conclusions: Evaluation of future iterations of this innovative program should address attendance and provider behavior change as well as patient and community outcomes associated with ECHO participation.